Memories in cities through the performance of festival processions - Das, Deepak; ., . (International Journal of Engineering and Technology, 2018)
The paper explores the idea of memories in cities. In the present scenario of globalised settlements, the rapid time-space and vast landscape of conurbation compression how memories are sustained in physical form. Historic landmarks (sites of memory) provide a medium to locate memory but they are viewed as objects. The city becomes a palimpsest with layers of history, events such as festival procession work as an instrument to link people to their past and these sites of memory. Various aspects of spatial framework influence and are influenced by festival procession. The static part of the built environment actively participates with the kinetic nature of procession.The study analyses the kinetic nature of procession and its performance to understand the production of memory and its spatialisation. Moreover, it demonstrates impact remembrance on urban form. Nature of memory is dynamic which change with alternation in processional rituals and built environment. Processional movement and performance develop perceivable spaces and create an association to sites of memory.Â Â